Physical activity level in people with Down Syndrome: a systematic review - Pietro Nobre Montoro, Ana Paula Pietro (2015)
Objective: To investigate the physical activity levels in individuals with Down Syndrome, through a systematic review. Methods: The search was performed in MEDLINE/PubMed, LILACS, and SciELO databases, following the adopted inclusion and exclusion criteria. Results: Five studies were selected for the study, with a sample of 344 participants aged 8-70 years. Among the findings, the studies presented varied physical activity practice and levels, according to each age group. In general, individuals with Down Syndrome present particularly low levels of physical activity and sharp decline with age. Conclusion: The individuals with Down Syndrome perform low level of physical activity, with lower rates than the recommendations for an active life. Moreover, it was found that, as age advances, the physical activity level decreases. There was a small number of researches addressing this issue. Thus, further studies should be conducted with the aim of assessing the level of physical activity in this population.